2008
DOI: 10.1108/02651330810877243
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐cultural examination of the relationships among firm reputation, e‐satisfaction, e‐trust, and e‐loyalty

Abstract: Purpose -The purpose of this paper is to empirically compare the impact of firm reputation on consumers' evaluation of e-tailers' market response outcomes (satisfaction, trust, and loyalty) in two cultures, the USA (individualism, low uncertainty avoidance, low context, and high-trust society) and South Korea (collectivism, high uncertainty, high context, and low-trust society). Design/methodology/approach -Two sets of data were collected, one in the USA and the other in Korea, using a mall intercept method. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
200
7
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(236 citation statements)
references
References 43 publications
20
200
7
9
Order By: Relevance
“…This result could be interpreted as contrary to previous studies which found that the relationship between satisfaction and loyalty is stronger in collectivists cultures with greater uncertainty avoidance (Jin et al, 2008). It would also confirm Van Birgelen, De Ruyter, De Jong, and Wetzels (2002) who affirm that in studies of consumer behaviour, the empirical results concerning national culture and services are not always consistent and univocal.…”
Section: Discussion Conclusion and Limitationscontrasting
confidence: 56%
See 2 more Smart Citations
“…This result could be interpreted as contrary to previous studies which found that the relationship between satisfaction and loyalty is stronger in collectivists cultures with greater uncertainty avoidance (Jin et al, 2008). It would also confirm Van Birgelen, De Ruyter, De Jong, and Wetzels (2002) who affirm that in studies of consumer behaviour, the empirical results concerning national culture and services are not always consistent and univocal.…”
Section: Discussion Conclusion and Limitationscontrasting
confidence: 56%
“…On the other hand, in the literature we find studies of other sectors of activity that have analyzed the moderator effects of the uncertainty avoidance and individualism/collectivism dimensions. In respect of uncertainty avoidance, moderator effects have been identified in repurchase intentions (Wong, 2004), in the relationships between perceived service quality and satisfaction (Reimann, Lünemann, & Chase, 2008), between satisfaction and loyalty (Jin et al, 2008;Liu et al, 2001). As regards the moderator effects of individualism/collectivism, these have been identified in the relationships between satisfaction and loyalty (Liu et al, 2001) and between attitude (affective loyalty) and intention (conative loyalty) (Kacen & Lee, 2002).…”
Section: [Table 1]mentioning
confidence: 99%
See 1 more Smart Citation
“…The original point of the present framework compared to existing models is that it is categorized around the concept of purchase, which is theorized as a process and not a one-time event. Existing theories have focused on the analysis of online consumer behaviour around e-service quality [15,234] or e-commerce in general [113,139,214], offering important classifications but neglecting to signify the importance of the ultimate consumer action [9], which is loyalty behaviour [145]. This new approach has immediate managerial implications, discussed below.…”
Section: Resultsmentioning
confidence: 99%
“…The seller of the product is trustworthy. [27,36] Trust (Ability) Social commerce site is competent Social commerce site knows about products in the social commerce. Social commerce site knows how to provide excellent service.…”
Section: Seller Reputationmentioning
confidence: 99%